The Effects of Intellectual Capital and Knowledge Management Processes on Dynamic Capabilities of the Organizations - MUHAMMAD, REBER ANWAR; SALMA, NIHAT (The journal of contemporary issues in business and government, 2021)
Intellectual capital and knowledge management explain the company’s performance. It is a very important dimension to improve the company’s dynamic capabilities and performance based on those factors. In addition, the aim of this paper is to investigate the relationship between intellectual capital, knowledge capacity, and dynamic capability, also the relationship between intellectual capital and knowledge capacity as well. To do these 178 data have been conducted across companies in the region. Based on the result, it has been observed that intellectual capital has a strong and significant impact on dynamic capabilities, also knowledge capacity has a significant impact on dynamic capability, eventually intellectual capital has also a significant impact on dynamic capability. It is suggested that the company owners and top managers should provide healthy and enough knowledge and intellectual capital.